EKSISTENSI KHIYAR DALAM UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI TOKO MODERN (Analisis Hukum Ekonomi Syariah) - Rahmatul Huda (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
Indonesia is a country that is predominantly Muslim, so that Muslim consumers certainly get the protection of the goods and/or services in accordance with Islamic law. Because the protection of the rights of every citizen of Indonesia. Khiyar is one form of consumer protection in Islam. Surely, khiyar as one of the forms to protect the rights of Muslim consumers are contained in the Consumer Protection Law. This thesis aims to determine: (1) Existence khiyar in Law No. 8 of 1999 on Consumer Protection, and (2) Analysis of the existence of khiyar in Law No. 8 of 1999 on Consumer Protection. This research is a normative law (normative legal research), namely legal research conducted by examining the legal material. The approach taken in this study is the statute approach and the conceptual approach. Based on the method used produced the conclusion that the existence khiyar in Law No. 8 of 1999 on Consumer Protection, contained in article 4, which khiyar ‘aib and khiyar syarath with the right to safety (article 4 letter a), khiyar majlis and khiyar ta'yin with the right to choose (article 4 letter b), khiyar tadlis and khiyar ‘aib with the right to be informed (article 4 letter c and h), and khiyar ru'yah with the right to be heard (article 4 letter d ). Existence khiyar in article 4 of the Law No. 8 of 1999 on Consumer Protection in terms of the Islamic economic law in accordance with the rules of fiqh, maqasid shari'ah, and fiqh.